Analisis Pengambilan Keputusan dalam Menyikapi Isu Keamanan Digital (Notifikasi "No System is Safe") di PT Telkomsel - Harmen, Hilma; Limbong, Mhd. Syaikhan Nazri; Simare-mare, Stefhani Gresia; Bintang, Dita Agustina; Bangun, Karin Rimina; Harahap, Nesah Sartika; Nababan, Helon Hibri (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study examines the decision-making process of PT Telkomsel in addressing digital security challenges, particularly in the context of the alert “No System is Safe.” The main problem lies in the increasing cyber threats that jeopardize customer data, corporate reputation, and regulatory compliance, which cannot be mitigated solely by adopting international security standards. The research aims to analyze how decision-making theories, especially bounded rationality, are applied by Telkomsel when responding to uncertain and high-risk situations. Using a qualitative descriptive approach with a literature review method, data were obtained from scholarly journals, corporate policy documents, institutional reports, and media coverage related to digital security and organizational decision-making. The findings reveal that Telkomsel employs a combination of directive, analytical, conceptual, and behavioral decision-making styles, supported by rational, intuitive, participative, and bounded rationality approaches. This integration enables the company to balance speed, accuracy, and adaptability in managing cyber incidents. The study contributes by highlighting that effective digital security management in a large-scale telecommunication company depends not only on technical safeguards but also on the quality of organizational decision-making under uncertainty.